Ndarboy Genk Music Performing Arts Management on the 2022 Cidro Asmoro Album Tour - Alawi*, Nizar Ihza; Bachtiar, Hafid Zuhdan (Universitas Syiah Kuala, 2024)
Music is a form of artistic expression, serving as a manifestation of the creator's emotions through attention to melody, rhythm, expression, and harmony. The accompanying music can act as a balance for both the left and right hemispheres of the listener's brain. Each singer is supported by a management team to present and achieve the best outcomes in a performance art that involves task distribution from general to functional areas. This study aims to investigate the management of Ndarboy Genk's music performances during the 2022 Cidro Asmoro album tour, aiming to identify weaknesses and obstacles in the management of their musical performances. The research employs a qualitative descriptive approach. The management of the music group Ndarboy Genk encompasses elements and functions that are interconnected. Additionally, the underlying factors in the artistic management of the Cidro Asmoro album tour by Ndarboy Genk include implementing organizational arts management, the second factor being production management by Ndarboy Genk, and the third factor being Ndarboy Genk's execution of performance arts management.